2015
DOI: 10.1007/s10934-015-9997-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of magnetically recyclable MOF-5@SiO2@Fe3O4 catalysts and their catalytic performance of Friedel–Crafts alkylation

Abstract: Magnetic Fe 3 O 4 particles were synthesized by solvo-thermal method, and then hydrolysis method was used to encapsulate a compact layer of SiO 2 on the surface of Fe 3 O 4 particles. Finally, the magnetic MOF5@SiO 2 @Fe 3 O 4 catalysts were prepared by in situ coating different contents of MOF-5 on the surface of SiO 2 @Fe 3 O 4 particles. The as-synthesized samples were characterized by TEM, SEM, XRD, FT-IR, N 2 adsorption/desorption, VSM and NH 3 -TPD. The catalytic activities of the magnetic MOF-5@SiO 2 @F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…MOFs having innovative characteristics can also be obtained by introducing nanomaterials in their framework. Magnetic nanoparticles (MNs) combined with MOFs lead to magnetic framework composites (MFCs) that result in stimuli responsiveness and could be utilized “on demand” for targeted drug delivery, selective separation, catalysis, and sensing. For example, Tan et al reported the fabrication of HKust-1/Fe 3 O 4 composite, by a dry gel conversion strategy, for the purification of hydrocarbon fuels, and Li et al synthesized a novel magnetically recyclable MOF catalyst for Friedel–Crafts alkylation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOFs having innovative characteristics can also be obtained by introducing nanomaterials in their framework. Magnetic nanoparticles (MNs) combined with MOFs lead to magnetic framework composites (MFCs) that result in stimuli responsiveness and could be utilized “on demand” for targeted drug delivery, selective separation, catalysis, and sensing. For example, Tan et al reported the fabrication of HKust-1/Fe 3 O 4 composite, by a dry gel conversion strategy, for the purification of hydrocarbon fuels, and Li et al synthesized a novel magnetically recyclable MOF catalyst for Friedel–Crafts alkylation …”
Section: Introductionmentioning
confidence: 99%
“…16−19 For example, Tan et al reported the fabrication of HKust-1/ Fe 3 O 4 composite, by a dry gel conversion strategy, for the purification of hydrocarbon fuels, 18 and Li et al synthesized a novel magnetically recyclable MOF catalyst for Friedel−Crafts alkylation. 19 In relation to biomedical applications, MFCs are very promising for engineering and development of biomedical theranostic systems due to their exclusive properties, including (a) exceptionally high surface area and porosity, which permit the loading of large amounts of active molecules with respect to existing materials, that show poor drug loading limited to the , heat release for hyperthermal therapy); and (f) possible engineering as contrast agents for multimodal imaging in diagnostics. 16 Studies on MFCs are recent, and only a few works are reported on their applicability in the biomedical field.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work on magnetic nanoparticle‐COF composites has been developed for synthesizing COFs for adsorption and removal of pollutants in water and food, [ 280,281 ] purification of hydrocarbon fuels [ 282 ] and catalysis, [ 283 ] and then using the magnetic component to allow the separation of these materials from solution. For COFs, the typical approach taking place is the encapsulation method of the NPs which is typically performed chemically: A first step involves functionalizing the nanoparticles surface either with an organic linker, [ 284,285,286 ] or with silica [ 283 ] and then the organic framework is grown on top of the particles. One such method was implemented by synthesizing dopamine‐capped iron oxide NPs, which afterward reacted with a COF building block triformylphloroglucinol (Tp).…”
Section: Inorganic Magnetic Nanoparticle–organic/organometallic Compositesmentioning
confidence: 99%
“…First the metal ions for the MOF (Cu or Fe) were bound to the carboxylic group on the iron oxides surface, and then this was further reacted with the benzenetricarboxylic acid units to form the MOF. [279] Recent work on magnetic nanoparticle-COF composites has been developed for synthesizing COFs for adsorption and removal of pollutants in water and food, [280,281] purification of hydrocarbon fuels [282] and catalysis, [283] and then using the magnetic component to allow the separation of these materials from solution. For COFs, the typical approach taking place is the encapsulation method of the NPs which is typically performed chemically: A first step involves functionalizing the nanoparticles Figure 10.…”
Section: Magnetic Nanoparticle-organic Framework Compositesmentioning
confidence: 99%
See 1 more Smart Citation